Living apart together. A ceramic analysis of Eastern Crete during the advanced Late Bronze Age - Langohr , Charlotte (Journal of Greek Archaeology, 2019)
During the Late Minoan (hereinafter LM) II to IIIB phases, roughly between 1450 and 1200 BCE, Cretan society went through a series of changes, the causes and circumstances of which are still the subject of dispute. One of the key issues that remains is the question of the cultural identity or identities of Cretan communities after the widespread, violent destructions of the LM IB palatial centres and settlements on the island. This discussion involves a debate on the long-standing and complex relationship between Crete and the Mycenaean Mainland. It is generally assumed that rulers from Central Greece or at least elite groups originating from this area took over the palace at Knossos during or after the Neopalatial (Middle Minoan III-LM I) collapse (or even caused it) and gradually acquired political control over much of the island with the establishment of a new centralised, Greek-speaking administration using the script Linear B, while also initiating abrupt cultural changes within Minoan society.